Analysis and Redesign of Al Tatbeqea Faculty - Fayez R Abu Safaqa; Saleh M Nassasra (My University, 2016)
The Applied college is an educational modern building which was designed to fit up with its uses, it consist of many of facilities such as computer labs, classrooms, head officer rooms.. etc.  it is located in khadoorie university in  Tulkarem Governorate, and consisted of four floors, each floor is 3.2 m high with an approximate area of 1282 m2 for each. Its now have already been  constructed. This structure was analyzed for seismic, and static loads using three dimensional modeling using SAP2000 software. also a handle analysis for static loads and for seismic load was made to get a preliminary dimension to be used in the calculations of the elements stiffness  before modeling the structure by SAP, and then the  result were verified by SAP2000.After the analysis of the project , the members were designed.

-- , . 1282   , 3.2   2000. "" . .
Analysis and Redesign of Al Tatbeqea Faculty